1997
DOI: 10.1073/pnas.94.15.8162
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis B virus X gene induces p53-mediated programmed cell death

Abstract: The human hepatitis B virus (HBV) protein pX is a multifunctional regulatory protein that is known to affect both transcription and cell growth. Here we describe induction of apoptosis in NIH 3T3 polyclonal cell lines upon stimulation of pX expression from a dexamethasone inducible mouse mammary tumor virus (MMTV)-X expression vector. The effect of long-term pX expression on the cell survival of mouse fibroblasts was confirmed in colony generation assays. This effect is not shared either by the other HBV produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
143
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(161 citation statements)
references
References 51 publications
16
143
2
Order By: Relevance
“…HBx can also exert antiapoptotic functions independently of p53 via modulation of activities of the serine protease hepsin (Zhang et al, 2005a) and upregulation of survivin (Li et al, 2003). HBx protein may also promote apoptosis dependent on p53 (Chirillo et al, 1997) or by regulating the expressions of Fas/FasL (Terradillos et al, 1998;Shin et al, 1999;Lee et al, 2002;, inactive procaspase-8, cFLICE (Kim and Seong, 2003), Bax/Bcl-2 (Miao et al, 2005), HSP60 (Tanaka et al, 2004), UV-DDB1 (Sitterlin et al, 2000;Bergametti et al, 2002;Leupin et al, 2003) and c-myc gene (Kalra and Kumar, 2004). HBx negatively regulates proteasome function and, thus, controls degradation of cellular and viral proteins (Sirma et al, 1998;Hu et al, 1999;Zhang et al, 2004).…”
Section: Hbxmentioning
confidence: 99%
“…HBx can also exert antiapoptotic functions independently of p53 via modulation of activities of the serine protease hepsin (Zhang et al, 2005a) and upregulation of survivin (Li et al, 2003). HBx protein may also promote apoptosis dependent on p53 (Chirillo et al, 1997) or by regulating the expressions of Fas/FasL (Terradillos et al, 1998;Shin et al, 1999;Lee et al, 2002;, inactive procaspase-8, cFLICE (Kim and Seong, 2003), Bax/Bcl-2 (Miao et al, 2005), HSP60 (Tanaka et al, 2004), UV-DDB1 (Sitterlin et al, 2000;Bergametti et al, 2002;Leupin et al, 2003) and c-myc gene (Kalra and Kumar, 2004). HBx negatively regulates proteasome function and, thus, controls degradation of cellular and viral proteins (Sirma et al, 1998;Hu et al, 1999;Zhang et al, 2004).…”
Section: Hbxmentioning
confidence: 99%
“…Results obtained using the lacZ reporter gene (right) are expressed as in (B) (Bergametti et al, 1999;Chirillo et al, 1997;Kim et al, 1998;Su and Schneider, 1997) although both the underlying mechanism and the biological signi®cance of these e ects are still elusive. Moreover, in several studies, HBx overexpression has been shown to directly trigger apoptosis, resulting in strong suppression of colony formation (Chirillo et al, 1997;Kim et al, 1998). In agreement with the latter observations, transfection into CCL-13 cells of an episomic vector (pDR2) carrying the wt WHx gene, reduced e ciency of hygromycin-resistant colony formation, in a dosedependent way ( Figure 4A).…”
Section: X-uvddb Interaction Is Involved In X-mediated Apoptosismentioning
confidence: 99%
“…In others, X appears to act far more upstream, by modulating the signal transduction cascade in the cytoplasm (Benn et al, 1996;Chirillo et al, 1996;Henkler et al, 1998;Kekule et al, 1993;Klein and Schneider, 1997;Lee and Yun, 1998;Su and Schneider, 1996). In addition to its widely documented transactivation activity, X has been reported to interfere with DNA repair (Becker et al, 1998;Wang et al, 1994), cell cycle control (Benn and Schneider, 1995) and apoptosis (Bergametti et al, 1999;Chirillo et al, 1997;Kim et al, 1998;Su et al, 1998). However, the functional connections between these activities and the cellular Xbinding proteins are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…HBx was shown to sequester the p53 protein in the cytoplasm and to inactivate its transactivating and apoptotic properties (Elmore et al, 1997;Takada et al, 1997;Truant et al, 1995;Wang et al, 1994Wang et al, , 1995. In other reports however, inhibition of known cellular functions of p53 could not be evidenced in cells with replicative HBV (Puisieux et al, 1995), and the apoptotic activity of the X gene product was found to require wild-type p53 (Chirillo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In human HBV carriers, HBx expression is preferentially maintained through the multistage process from preneoplastic nodules to HCC and peritumoral tissues (Su et al, 1998) and X-speci®c mRNAs selectively accumulate in liver tumors from HBsAg-negative patients (Paterlini et al, 1995). Relevant to how HBx might participate in cell transformation, the X gene product stimulates cell cycle progression, DNA synthesis and apoptosis (Benn and Schneider, 1995;Chirillo et al, 1997;Su and Schneider, 1997). There is also evidence to indicate that HBx may bind a variety of cellular target genes (Fischer et al, 1995;Lee et al, 1995;Sirma et al, 1998), and notably the tumor suppressor protein p53 (Feitelson et al, 1993;Lin et al, 1997;Ueda et al, 1995).…”
Section: Introductionmentioning
confidence: 99%